Recent Advances in Transition-Metal-Catalyzed Reactions of N-Tosylhydrazones - Vaishya, V.; Singhal, R.; Kriplani, T.; Pilania, M. (Synthesis, 2022)
N-Tosylhydrazones are highly versatile precursors for in situ carbene formation and are frequently used in metal-catalyzed cross-coupling reactions. Due to their many applications in organic synthesis, including C–C, C–O, C–N, and C–S bond formation, N-tosylhydrazones have recently received much interest. They can be simply synthesized by reacting an aldehyde or ketone with N-tosylhydrazine to produce a solid N-tosylhydrazone, which is a ‘green’ precursor of diazo compounds. Using a suitable metal catalyst, N-tosylhydrazones show versatile substrate scope for the synthesis of substituted diaminopyrroles, chromenopyrazoles, alkenylpyrazoles, benzofuran thioethers, tetrahydropyridazines, sulfur-containing heterocycles, and benzofurans with potent biological activities and even regioselective N-functionalization reactions. Metal-catalyzed reactions of N-tosylhydrazones for the construction of bioactive heterocycles are still highly in demand. Hence, this review focuses on the recent synthetic application of N-tosylhydrazones influenced by different transition metals with notable features like simple workup procedures, gram-scale synthesis, broad substrate scope, multicomponent processes, cyclization, and carbon–heteroatom bond formation.1 Introduction2 Applications of N-Tosylhydrazones3 Conclusion
Keywords: N-tosylhydrazone; cross-coupling reaction; regioselective; carbene; cycloaddition; olefination